2018
DOI: 10.1039/c8cp01235k
|View full text |Cite
|
Sign up to set email alerts
|

CsPbBr3 and CH3NH3PbBr3 promote visible-light photo-reactivity

Abstract: Inorganic and organic lead halide perovskite materials attract great interest in the scientific community because of their potential for low-cost, high efficiency solar cells. In this report we add a new property of these materials, namely their photochemical activity in the visible light range. Both inorganic (CsPbBr3) and organic (CH3NH3PbBr3-MAPbBr3) perovskite thin films were demonstrated to promote photo-dissociation of adsorbed ethyl chloride (EC), employing 532 nm pulsed laser irradiation under ultra-hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…activities, electrochemical water splitting, as well as solar cells and tandem solar cells [3][4][5][6][7][8].…”
Section: Applied Bias (V)mentioning
confidence: 99%
“…activities, electrochemical water splitting, as well as solar cells and tandem solar cells [3][4][5][6][7][8].…”
Section: Applied Bias (V)mentioning
confidence: 99%
“…In a typical photoreactivity (using 532 nm pulsed laser) demonstration to promote the dissociation of adsorbed ethyl chloride under ultra-high vacuum (UHV) conditions on the surfaces of the both inorganic (CsPbBr 3 ) and HOIP (CH 3 NH 3 -PbBr 3 -MAPbBr 3 ) thin lms, it was shown that the photoreactivity on the inorganic surface is more efficient than on the hybrid perovskite surface, which is attributed to the lower density of defects and surface states in CsPbBr 3 than in MAPbBr 3 . 50 A schematic of the overall photoreactivity on the surfaces of both CsPbBr This journal is © The Royal Society of Chemistry 2022 photocatalyzation of the a-alkylation reaction, with a high yield and a turnover number (TON) of over 52 000, which is higher in magnitude (3 orders) than precious Ir or Ru catalysts using CsPbBr 3 NCs (see Table 3). CsPbBr 3 NCs emissive colloid suspensions with sizes and photoluminescence lifetimes of 2-100 nm and $10 to $100 ns, respectively, were synthesized by a single-pot emulsion/de-emulsion effect (Fig.…”
Section: Cspbbr 3 Pncs In Organic Transformationsmentioning
confidence: 99%
“…In a typical photoreactivity (using 532 nm pulsed laser) demonstration to promote the dissociation of adsorbed ethyl chloride under ultra-high vacuum (UHV) conditions on the surfaces of the both inorganic (CsPbBr 3 ) and HOIP (CH 3 NH 3 PbBr 3 –MAPbBr 3 ) thin films, it was shown that the photoreactivity on the inorganic surface is more efficient than on the hybrid perovskite surface, which is attributed to the lower density of defects and surface states in CsPbBr 3 than in MAPbBr 3 . 50 A schematic of the overall photoreactivity on the surfaces of both CsPbBr 3 and CH 3 NH 3 PbBr 3 is shown in Fig. 2a.…”
Section: Pncs In Organic Transformationsmentioning
confidence: 99%
“…In particular, one of the most emerging applications of AIHP materials is with regard to the wastewater purification process of textile effluents from industrial production. , In this field, heterogeneous catalysis under light is widely accepted due to its high efficiency, yield of degradation, and cost effectiveness. Moreover, CsPbX 3 (X = Cl, Br, I) perovskites, in the form of quantum dots (QDs), show photoelectrochemical degradation processes of different organic dye compounds , and high performance in hydrogen evolution under visible-light irradiation . In addition, it has been widely demonstrated that CsPbBr 3 nanocrystals are also exceptional candidates as photocatalysts for fundamental organic reactions: for example, C–C, C–N, and C–O bond formations and CO 2 reduction. , Finally, CsPbBr 3 and CsPb 2 Br 5 have been deeply studied as highly stable humidity sensor systems …”
Section: Introductionmentioning
confidence: 99%
“…39,40 In this field, heterogeneous catalysis under light is widely accepted due to its high efficiency, yield of degradation, and cost effectiveness. Moreover, CsPbX 3 (X = Cl, Br, I) perovskites, in the form of quantum dots (QDs), show photoelectrochemical degradation processes of different organic dye compounds 41,42 and high performance in hydrogen evolution under visible-light irradiation. 43 In addition, it has been widely demonstrated that CsPbBr 3 nanocrystals are also exceptional candidates as photocatalysts for fundamental organic reactions: for example, C−C, C−N, and C−O bond formations 44 and CO 2 reduction.…”
Section: Introductionmentioning
confidence: 99%